Neutrosophic Sociogram Approach to Neutrosophic Cognitive Maps in Swift Language - R. Priya; Nivetha Martin (Neutrosophic Sets and Systems, 2022)
Neutrosophic Cognitive Maps (NCM) decision-making system encompasses sequential tasks of resolving the confrontations in finding the ideal solution. This paper introduces neutrosophic sociogram (NS) approach as an alternative to the conventional approach of NCM in finding the fixed point of the dynamical NCM system. A comparative analysis is made between two approaches and the efficiency of the proposed approach is validated with an application to find the interrelationship between the persuading eleven factors of Technopreneurship. It was observed that the results obtained using the proposed approach is more compatible, feasible and simple than the conventional approach in making decisions on the implications between the factors. The two approaches are programmed using SWIFT language to make the computations easier and the results are in consensus with the manual calculations.